Practical Guide to Information Systems Process Improvement, A - Cassidy, Anita (CRC Press, 2009)
When you invest in expensive technology and systems, you want to get the most out of them. Process improvement has been used for years as an effective strategy to reduce costs, shorten cycle times, improve quality, and increase user satisfaction in other areas of business such as Quality, Manufacturing, and Engineering. While there are many books available on process improvement and process re-engineering, few of them address the unique processes within information systems as clearly and succinctly as A Practical Guide to Information Systems Improvement.